Hierarchically Structured Zn-Al LDH/Hydrochar from Rambutan Peel (Nephelium lappaceum L.) for Enhanced Fe(II) Adsorption - Erviana, Desti; Normah, Normah; Arieveali, Heroldinho; Ramadhan, Navinda (Science and Technology Indonesia, 2026)
Dissolved ferrous ions in water pose significant environmental and operational challenges, necessitating efficient and sustainable removal technologies. In this study, a hybrid adsorbent was developed by integrating Zn-Al layered double hydroxide (LDH) with hydrochar derived fromrambutan peel (Nephelium lappaceum L.) via coprecipitation. Characterization confirmed successful composite formation with a substantial increase in specific surface area from 9.621 m2.g-1 for pristine Zn-Al LDH to 52.964 m2.g-1 for the composite, accompanied by enlarged pore volume and enriched oxygen-containing functional groups. Batch adsorption experiments showed strong pH dependence, with optimal Fe(II) removal at pH 6 and equilibrium reached within 120 min. The Zn-Al LDH@NL-HC composite exhibited a markedly higher adsorption capacity (51.501 mg.g-1) compared with Zn-Al LDH (15.692 mg.g-1) and hydrochar alone (8.594 mg.g-1), indicating a significant synergistic effect. Isotherm analysis revealed a maximum adsorption capacity of 76.336 mg.g-1 at elevated temperature, while kinetic data followed a pseudo-second-order model, suggesting chemisorption-dominated uptake. Thermodynamic parameters indicated an endothermic and spontaneous process. Regeneration studies demonstrated excellent stability, with adsorption efficiency maintained at 79.48% after five cycles. The superior performance is attributed to combined mechanisms including electrostatic attraction, surface complexation with oxygen-rich groups, ion exchange within LDH interlayers, and diffusion into mesoporous structures. These findings demonstrate the effective valorization of agricultural waste into a high-performance and reusable adsorbent for Fe(II) remediation in aqueous systems.